THE INFLUENCE OF THIRD PARTY FUNDS, CAPITAL ADEQUACY RATIO, NON PERFORMING LOANS TO CREDIT DISTRIBUTION ON THE INDONESIA STOCK EXCHANGE - Langodai, Desyana Jari; Lutfillah, Novrida Qudsi (RIMA - Research In Management and Accounting, 2019)
The influence of third party funds, capital adequacy ratio, non-performing loans to credit distribution on the Indonesia Stock Exchange period 2013-2017. This study aims to examine and analyze the effect of DPK, CAR, NPL on lending. This data was obtained from the official website of the Indonesia Stock Exchange website. The sampling technique uses purposive sampling. Data analysis was performed using statistics with SPSS 21 tools. The research findings show that the calculated t-value results from DPK 15,84 with a significance level 0,000 which means DPK has a positive and significant effect. While CAR and NPL do not have a significant effect on lending because the significance value is greater that 5%. While simultaneously DPK, CAR, NPL affect credit distribution with a significance level of 0,000.